Exploring the Dynamics of Spiritual Life in Residential Care Communities. Issue 2 (November 2015) - Kartupelis, Jenny
Abstract : This article is designed to offer some insights into the nature of individual and communal spiritual life in care homes and sheltered housing for older people, and to explore critical points of interaction between the social and physical environment, and spiritual flourishing. It draws on a series of surveys commissioned by the Abbeyfield Society, a charity that provides a range of care and accommodation in the UK and overseas. The reports arising from the surveys are based on approximately 100 interviews, each private and semi-structured, with residents, managers, care workers, volunteers and trustees. They indicate how needs that directly affect spiritual health may be met, in terms of current practice and future planning; and identify the key relational factors that lead to the transformation of lives in community settings.